Language identity in the Singaporean context - Yee, Jia'en (2015)
This study aims to validate a survey tool and visualisation technique that enables us to obtain a detailed “language fingerprint” for individuals, which would reflect the linguistic diversity in Singapore - a feature of the bilingual context which is often overlooked. This tool would chart out the language background of individuals, and reveal a unique language identity that differs from person to person. The information to be collected includes the languages used by individuals, the duration of exposure to the languages, self evaluations of language proficiency, language preferences, how they feel about their languages, as well as contexts in which the languages are used. The study will also document who spoke which languages how much to the participants as they were growing up, allowing a measure of how language input in childhood contributes to the individual’s language identity. Taken together, this study identified patterns of language “knowledge” of Singaporeans, as well as their consumption behaviors in relation to reading, watching, listening and writing. It is also found that early language input in the form of age of acquisition (AoA), language mix and years of use are significant predictors of language proficiency in an individual’s later years, and do correlate to consumption behaviours in the areas of reading, watching and listening.